Management of pigeon pea in short fallows for crop-livestock production systems in the Guinea Savanna zone of northern Ghana - Agyare, Wilson Agyei; Kombiok, J.M.; Karbo, N.; Larbi, Asamoah (Springer, 2002)
Crop and livestock production in the Guinea savanna zone of northern Ghana has been declining over the past years as a result of increasing pressure on land. To sustain soil productivity, pigeon pea (Cajanus cajan), a leguminous perennial crop was evaluated for its potential as a short duration fallow crop for fodder and grain, and maize (Zea mays) production. It involved comparing a natural fallow (i.e., control) and four improved fallows of pigeon pea pruned annually at 30 cm, 60 cm and 90 cm from the ground, and unpruned pigeon pea over a two-year period. After this time, the land was cleared manually and planted to maize. The highest mean annual biomass of pigeon pea over the two-year period of 6.1 t ha' dry matter (DM) was obtained by pruning at 60 cm. The highest leaf litter production and pigeon pea seed yield was obtained from the no pruning treatment. The mean maize grain yield from the improved fallow (3.02 t ha ') in the first year after clearing was significantly (P < 0.05) greater than that of the natural fallow (1.54 t ha '). Considering the biomass of pigeon pea from pruning, pigeon pea seed yield and maize grain yield after the pigeon pea, pruning pigeon pea at 60 cm is the most promising regime for crop-livestock production systems.